Inconsistency in Law Enforcement on Torture by Authorities: The Urgency of Harmonizing the Criminal Code and the Anti-Torture Convention - Humu, Cendris; Fujiyana Khoerunisa, Arien (Universitas Negeri Gorontalo, 2025)
This article aims to analyze the inconsistency in law enforcement regarding the practice of torture by law enforcement officers in Indonesia, as well as to examine the urgency of harmonizing the Indonesian Criminal Code (KUHP) with the Convention Against Torture. This study uses a normative juridical method with an approach based on legislation, conceptual analysis, and concrete cases. The discussion reveals that the practice of torture by law enforcement officers reflects a systemic pattern of violence, driven by weak regulations in the KUHP, suboptimal monitoring mechanisms, and a strong culture of impunity. Although Indonesia has ratified the Convention Against Torture, the absence of specific provisions on the crime of torture in the KUHP, the failure to ratify the Optional Protocol (OPCAT), and the delayed revision of the Criminal Procedure Code (KUHAP) are the main factors behind the failure to prevent and enforce accountability. This article recommends comprehensive reforms through the revision of the KUHP and KUHAP, ratification of the OPCAT, strengthening independent monitoring bodies, and a shift in the paradigm of law enforcement officials to respect human rights principles in order to effectively eliminate the practice of torture in Indonesia.